2011
DOI: 10.1038/nn.2758
|View full text |Cite
|
Sign up to set email alerts
|

Ventral medial prefrontal cortex neuronal ensembles mediate context-induced relapse to heroin

Abstract: In a rat model of context-induced relapse to heroin, we identified sparsely distributed ventral medial prefrontal cortex (mPFC) neurons that were activated by the heroin-associated context. Selective pharmacogenetic inactivation of these neurons inhibited context-induced drug relapse. A small subset of ventral mPFC neurons forms neuronal ensembles that encode the learned associations between heroin reward and heroin-associated contexts; re-activation of these neuronal ensembles by drug-associated contexts duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
333
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(367 citation statements)
references
References 14 publications
30
333
2
2
Order By: Relevance
“…Our observation that Fos activation was greater in the infralimbic than prelimbic cortex of adult rats during heroin-seeking is consistent with a greater role for the infralimbic than prelimbic region in heroin-seeking (Van den Oever et al, 2008;Bossert et al, 2011), but contradicts theories based mainly on cocaine-related behavior that the infralimbic cortex inhibits drug-seeking, whereas the prelimbic cortex promotes it (Peters et al, 2009). For both subregions, we also observed activation in only a small percentage of neurons during heroin-seeking, similar to the 5-7% activation reported previously (Bossert et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our observation that Fos activation was greater in the infralimbic than prelimbic cortex of adult rats during heroin-seeking is consistent with a greater role for the infralimbic than prelimbic region in heroin-seeking (Van den Oever et al, 2008;Bossert et al, 2011), but contradicts theories based mainly on cocaine-related behavior that the infralimbic cortex inhibits drug-seeking, whereas the prelimbic cortex promotes it (Peters et al, 2009). For both subregions, we also observed activation in only a small percentage of neurons during heroin-seeking, similar to the 5-7% activation reported previously (Bossert et al, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, measured behavior could be called 'extinction responding in the absence of discrete drug-paired cues'. Although reexposure to the drug selfadministration environment (context) is likely to be the stimulus driving any lever-pressing we might observe in these conditions, our methods differ from those of Shaham et al (2003) that provide precise tests of context-induced reinstatement that involve daily exposure to an alternative environment during forced abstinence (eg, Bossert et al, 2011).…”
Section: Heroin Self-administration and Heroin-seeking Proceduresmentioning
confidence: 99%
“…Further evidence for a role of the mPFC in relapse comes from animal studies, where drugassociated mPFC activity has been shown to provoke relapse to diamorphine (66). In humans, relapse in AD has been associated with enhanced cue-related activity in the mPFC (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral aHPC and pHPC ROIs were defined following a prior study of aHPC and pHPC connectivity (Chen and Etkin, 2013), taking the anterior-most third and posterior-most third of an HPC ROI consisting of voxels with a 460% likelihood of being in HPC (as defined by the Harvard-Oxford probabilistic structural axis). The following additional ROIs, chosen a priori based on preclinical research (Bossert et al, 2011;Fuchs et al, 2005;McLaughlin and See, 2003;Otis et al, 2014), our previous neuroimaging studies (McClernon et al, 2005(McClernon et al, , 2007(McClernon et al, , 2009) and metaanalysis (Engelmann et al, 2012;Kuhn and Gallinat, 2011;Tang et al, 2012) of cue-reactivity, were created in PickAtlas (Maldjian et al, 2003): (1) ventral striatum (5 mm radius sphere centered on ± 6,4, − 5); (2) amygdala (anatomical); (3) insula (5 mm radius sphere centered on ± 38,10,6); (4) mPFC inclusive of portions of rostral anterior cingulate cortex (5 × 10 × 10 mm box centered on ± 5, 40, 10); and (5) PCC (5 × 5 × 10 mm box centered on ± 5, − 60,20). See Supplementary Figure S3 for visual depictions of the ROIs selected for analyses.…”
Section: Fmri Data Analysismentioning
confidence: 99%
“…Neuropharmacological studies of drug-environment associations using these paradigms implicate brain regions broadly involved in conditioned reward including the amygdala, medial prefrontal cortex (mPFC), striatum, and insula (Bossert et al, 2011;Fuchs et al, 2005;McLaughlin and See, 2003;Otis et al, 2014). However, one region-the dorsal hippocampus (dHPC)-has been singled out as having a potentially selective and critical role in drugcontext learning (Fuchs et al, 2005;Meyers et al, 2003Meyers et al, , 2006Ramirez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%